A quest for the historical Christ: Scientia Christi and the modern study of Jesus - Giambrone, Anthony (The Catholic University of America Press, 2022)
Intro -- Contents -- Acknowledgments -- List of Abbreviations -- Introduction -- Part I. Historical Foundations -- 1. Vera et Sincera de Iesu -- 2. The German Roots of Historical Jesus Research -- 3. The "Lying Historians" and Luke 1-2 -- 4. Memorializing Miracles in the World of the Gospels -- 5. Eyewitness Historiography and the Resurrection -- Part II. Theological Perspectives -- 6. Spirit and Power -- 7. The Revenge of Alexandrian Exegesis: Toward an Ecclesial Hermeneutic -- 8. Interpretatio Iudaica -- 9. Primitive Christology as Ancient Philosophy -- 10. Two Loci of Greco-Roman Jewish Monotheism -- Part III. Jesus and the Scriptures -- 11. Scientia Christi: Three Theses -- 12. Another Johannine Thunderbolt? The Legatio Baptistae and "The Poetic Christ" -- 13. "Why Do the Scribes Say?" Scribal Expectations of an Eschatological High Priest and the Interpretation of Jesus' Transfiguration -- 14. Prosopological Exegesis and Christological Anagnorisis -- 15. Jesus' Prophetic Knowledge and the Gospels -- Appendix I: Anti-Hegelian Postlude on the Religion of the Future -- Appendix II: Review of Paula Fredriksen, When Christians Were Jews: The First Generation -- Bibliography -- Scriptural Index -- Ancient Sources Index -- Subject Index.